Maternal depression across the first years of life compromises child psychosocial adjustment; relations to child HPA-axis functioning. (February 2016) - Apter-Levi, Yael; Pratt, Maayan; Vakart, Adam; Feldman, Michal; Zagoory-Sharon, Orna; Feldman, Ruth
Highlights: Maternal depression was assessed repeatedly from birth to six years to form chronically-depressed and non-depressed groups. At six years, depressed mothers were more negative and their children showed greater psychopathology and social withdrawal. Children of depressed mothers exhibited reduced cortisol (CT) variability, implying no decrease in CT levels over time. Maternal depression and negative parenting predicted child baseline CT and CT variability. Child CT baseline and variability, in turn, predicted child psychopathology, social withdrawal, and empathy. Abstract: Maternal depression across the first years of life negatively impacts children's development. One pathway of vulnerability may involve functioning of the hypothalamic-pituitary-adrenal (HPA) axis. We utilize a community cohort of 1983 women with no comorbid risk repeatedly assessed for depression from birth to six years to form two groups; chronically depressed ( N = 40) and non-depressed ( N = 91) women. At six years, mother and child underwent psychiatric diagnosis, child salivary cortisol (CT) was assessed three times during a home-visit, mother-child interaction was videotaped, and child empathy was coded from behavioral paradigms. Latent Growth curve Model using Structural Equation Modeling (SEM) estimated the links between maternal depression and mother's negative parenting and three child outcomes; psychopathology, social withdrawal, and empathy as related to child CT baseline and variability. Depressed mothers displayed more negative parenting and their children showed more Axis-I psychopathology and social withdrawal. SEM analysis revealed that maternal depression was associated with reduced CT variability, which predicted higher child psychopathology and social withdrawal. Whereas all children exhibited similar initial levels of CT, children of controls reduced CT levels over time while children of depressed mothers maintained high, non-flexible levels. Mother negativity was related to lower initial CT levels, which predicted decreased empathy. Findings suggest that chronic maternal depression may compromise children's social-emotional adjustment by diminishing HPA-system flexibility as well as limiting the mother's capacity to provide attuned and predictable caregiving.